Study of Language Features Used by Male and Female in #SaveJohnnyDepp on Instagram and Twitter - Dewi Ginarti; Irman Nurhapitudin; Ruminda Ruminda; Hasanah Hj. Iksan (UIN Sunan Gunung Dajti Bandung, 2022)
This study aims to determine the language features used by male and female in social media, especially Instagram and Twitter. The data used in this study are based on ten characteristics of women's language features which presented by Robin Lakoff in her book entitled Language and Women's Place. This study also uses an additional theory about the characteristics of men’s language which is presented by Jennifer Coates as a supporter of the main theory. The data collected comes from Instagram and Twitter posts containing hashtag #SaveJohnnyDepp. The results showed that male and female users use the same language characteristics, but the frequency is slightly different. The difference lies in the focus of the topics discussed and the use of language features proposed by Lakoff and Coates. This study also found that the purpose of using #SaveJohnnyDepp on Instagram and Twitter both male and female users is to provide support and ask for the justice that Johnny Depp deserves.